Luminosity and Illusion in the Bardo - Ryan, Mark (Auckland University of Technology, 2008)
This is a creative practice-based photographically researched project that is contextualised by a written exegesis. I am attempting to conceptualise the apparent visual experiences that occur during the dying process, death, and rebirth as believed within Tibetan Buddhism. The Bardo of life is also relevant as it pre-ordains the visual context of the experiences within the dying, death and rebirth Bardos. Through the medium of photography, my methodology and practice are reflective of two fundamental ideas. These are: Luminosity and Illusion. They are supported by my research into the phenomenon of the 'Near Death Experience' and the Jungian concept of the conscious and subconscious mind. These states of reality are explored in relation to the Tibetan Book of the Dead's concept of the Bardo. My focus is to photograph the four elements of Earth, Fire, Air and Water as mediums familiar to all human beings and relate these in context to the Tibetan Book of the Dead's description of entering the Bardo of death. Illusion and luminosity are discovered by 'seeing' these within the four elements, and are related in context to the Tibetan Buddhists' belief of an after-death reality. This transition from the dying process into the unknown Bardo of death is supported by the familiarity of these four elements in life, and the mind's notion of reality.
Keywords: Luminosity; Illusion; Buddhism; Bardo; Death